RELEASE FROM MASKING: BEHAVIORAL AND ELECTROPHYSIOLOGICAL MEASURES IN YOUNG AND OLDER LISTENERS - Faucette, Sarah P. (East Carolina University, 2018)
Difficulty listening to speech under challenging conditions is the main complaint of audiology patients. Researchers have explored the cause of this concern, however, many questions are left unanswered. The primary concern of the present series of experiments is the contribution of temporal resolution to speech in noise processing. Specifically, the phenomenon of “release from masking”, the aptitude of the auditory system to make use of temporal gaps in competing signals, allowing for perception of target speech. In Experiment I, a commonly researched behavioral paradigm to measure temporal release from masking was explored in young and older normal hearing adults to determine the effect of noise type, aging, presentation level, and SNR on speech recognition. Words and sentences were presented in interrupted and continuous noises at varying intensities and signal to noise ratios. There was a significant effect of presentation level on interrupted noise benefit (i.e., release from masking). Higher intensities created improved understanding in interrupted noise. This finding suggests an intensity to exploit temporal abilities when completing behavioral assessments, particularly if evaluating temporal resolution through release from masking. It was also determined that younger adults were received greater perceptual advantage in interrupted noise than older adults, indicating an effect of age on temporal resolution despite continued normal hearing thresholds. Experiment II investigated neural encoding of this phenomenon through electrophysiological measures of the auditory cortex. Cortical auditory evoked potentials (CAEPs) were utilized to demonstrate interrupted noise benefit and explore the effect of SNR and age on this response. With the older adults exhibiting similar auditory thresholds as younger adults and yet displaying a clear temporal deficit in speech in noise understanding, Experiment II sought to determine if a deficit in neural encoding of these signals within the auditory cortex was evident. A speech stimulus (/da/) was used to elicit the CAEPs in interrupted and continuous noises. Decreased P1 and P2 latencies and increased N1 amplitudes were recorded in interrupted noise versus continuous noise, indicating a temporal benefit. These differences were considered a cortical release from masking. Identifying this response in a localized measure may lead to better understanding of the auditory cortex’s role in temporal processing of speech in difficult listening environments. With an increase in P1 and N1 amplitudes in older listeners, decreased neural inhibition was indicated. It is plausible that this aging affect could result in the temporal deficit measured behaviorally. A significant correlation between this electrophysiological finding and behavioral measures of the same deficit would confirm this theory. Experiment II was designed to explore the associations between the behavioral and electrophysiological measures of Experiments I and II. No clinically significant correlations were found between these measures. A failure to demonstrate this correlation brings into question the clinical utility of the electrophysiological measures of Experiment II. Significant correlations would have allowed for the electrophysiological response to be measured in lieu of behavioral assessment for those that are difficult to test due to physical and mental limitations. However, without a clear relationship, this electrophysiological response cannot be used in this fashion.
Keywords: Temporal resolution; cortical auditory evoked potentials; speech recognition in noise; aging; Auditory Perception; Evoked Potentials, Auditory